Canva and Google Maps Training for Printing MSMEs in Bandar Lampung City - Dewi, Citra; Fadly, Romi; Anisa, Rahma; Rahmadi, Eko (Indonesian Journal of Community Services Cel, 2024)
One of the post-pandemic impacts has been the near cessation of many businesses, including printing MSMEs (Micro, Small, and Medium Enterprises). The rapid advancement of the digital era also requires business actors, particularly MSMEs, to engage in public marketing to broaden their reach and make it easier for consumers to locate their business premises. Observations in the field reveal that some MSMEs are still unprepared for the changes brought about by digital marketing and promotion due to limited knowledge among their human resources. This community service activity aims to transfer technology and knowledge to printing MSMEs in Bandar Lampung City through training on using Canva and Google Maps software applications to support their business publicity. The method employed involved delivering materials and practical sessions, with pretests and posttests conducted to assess the participants' skills. Following the training, participants could design using Canva, and the locations of the printing MSMEs were successfully uploaded online. The training results showed a 34% increase in participants' understanding of the material presented.